2002
DOI: 10.1185/030079902125000101
|View full text |Cite
|
Sign up to set email alerts
|

The Onset of Action and the Analgesic Efficacy of Saridon®* (a Propyphenazone/Paracetamol/Caffeine Combination) in Comparison with Paracetamol, Ibuprofen, Aspirin and Placebo (Pooled Statistical Analysis)

Abstract: The objective was to evaluate the onset of action, analgesic efficacy and tolerability of Saridon*, a propyphenazone 150 mg/paracetamol 250 mg/caffeine 50 mg combination, in comparison with paracetamol 500 mg, aspirin 500 mg, ibuprofen 200 mg and placebo, by a pooled statistical analysis of eight studies. Out of 500 generally healthy patients (55.2% men, 44.8% women), average age 43.5 years, 329 (65.8%) had moderate and 171 (34.2%) severe acute dentoalveolar pain. More Saridon-treated patients reported 'pain g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…This procedure also allows post‐operative pain management using local anaesthetics, NSAIDs, and opioids, as reported in previously published dental studies 5 . Ibuprofen, a propionic acid derivative analgesic that provides anti‐inflammatory action, has been used in adult studies to evaluate its preoperative effect on post‐extraction pain relief following dental procedures 6,12–15 . It was found to be a safe and effective analgesic as an anti‐inflammatory agent in dosages ranging from 10 mg/kg/day to a maximum of 40 mg/kg/day 9 .…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…This procedure also allows post‐operative pain management using local anaesthetics, NSAIDs, and opioids, as reported in previously published dental studies 5 . Ibuprofen, a propionic acid derivative analgesic that provides anti‐inflammatory action, has been used in adult studies to evaluate its preoperative effect on post‐extraction pain relief following dental procedures 6,12–15 . It was found to be a safe and effective analgesic as an anti‐inflammatory agent in dosages ranging from 10 mg/kg/day to a maximum of 40 mg/kg/day 9 .…”
Section: Introductionmentioning
confidence: 91%
“…It was found to be a safe and effective analgesic as an anti‐inflammatory agent in dosages ranging from 10 mg/kg/day to a maximum of 40 mg/kg/day 9 . It reached the peak plasma concentration 30 min after administration 12–15 . Paracetamol is also a traditional antipyretic and analgesic drug, as characterized in textbooks.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, dopaminergic overactivity in the frontal cortex and underactivity in the limbic areas, can be treated simultaneously, alleviating both positive and negative symptoms of schizophrenia, respectively 46. Additionally, the finding that amisulpride is a highly effective antidepressant via antagonism at 5-HT 7 receptors would make its mechanism of action a unique one relative to other approved antidepressant drugs, and supports the development and/or testing of more selective 5-HT 7 receptor antagonists to treat depression in humans,16 including their effects on negative symptoms, cognitive dysfunction, mood, morbidity and mortality, work and social function, quality of life, and family and societal burden.…”
Section: Correlation Between Pharmacological Profile and Effects Of Amentioning
confidence: 99%
“…Langhauser et al went one step further and found that no treatment paradigm (prophylactic or therapeutic) and no model (transient or permanent) showed efficacy (Langhauser et al, 2014). On the other hand, both Becker, 2002 and Relton et al, 2000 found that inhibition of α 4 improved both infarct volumes and functional deficits. When a preclinical randomized control trial was implemented at multiple centers, researchers found efficacy only in patients with small infarct volumes (Llovera et al, 2015).…”
Section: Role Of Integrins Post-stroke: An Overviewmentioning
confidence: 98%
“…Though this mechanism is less obvious in the highly mobile leukocytes. Once leukocytes are bound to selectins, additional binding to integrins and adhesion molecules (intracellular adhesion molecule (ICAMs and vascular adhesion molecule-1 (VCAM) occurs, permitting leukocytic rolling (del Pozo et al, 1995; Lorant et al, 1995; Kindzelskii et al, 1996; Becker, 2002). Additional damage can occur once at the site of ischemia, as infiltration into the brain parenchyma across the BBB destroys surrounding vasculature (Clark et al, 1993; Chou et al, 2004), and leukocytes continually release additional factors (reactive oxygen species, cytokines, and proteases) that enhance leukocytic recruitment (Wang et al, 2008).…”
Section: Leukocytic Infiltration Following Ischemic Strokementioning
confidence: 99%